2023
DOI: 10.1038/s41586-022-05680-3
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell spatial immune landscapes of primary and metastatic brain tumours

Abstract: Single-cell technologies have enabled the characterization of the tumour microenvironment at unprecedented depth and have revealed vast cellular diversity among tumour cells and their niche. Anti-tumour immunity relies on cell–cell relationships within the tumour microenvironment1,2, yet many single-cell studies lack spatial context and rely on dissociated tissues3. Here we applied imaging mass cytometry to characterize the immunological landscape of 139 high-grade glioma and 46 brain metastasis tumours from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(123 citation statements)
references
References 61 publications
(90 reference statements)
2
103
0
Order By: Relevance
“…In this regard, Shaim et al reported that targeting the αv integrin/TGF-β axis helps enhance NK cell function against GBM stem cells in vitro [ 110 ]. Recently, Karimi et al found that a subset of neutrophil-like macrophages positive for myeloperoxidase (MPO) could be beneficial for the survival of GBM patients [ 223 ]. Thus, inhibiting the αv integrin/TGF-β axis or enhancing the population of MPO+ macrophages, along with employing known immunotherapeutic techniques, needs to be tested as an alternative glioma therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Shaim et al reported that targeting the αv integrin/TGF-β axis helps enhance NK cell function against GBM stem cells in vitro [ 110 ]. Recently, Karimi et al found that a subset of neutrophil-like macrophages positive for myeloperoxidase (MPO) could be beneficial for the survival of GBM patients [ 223 ]. Thus, inhibiting the αv integrin/TGF-β axis or enhancing the population of MPO+ macrophages, along with employing known immunotherapeutic techniques, needs to be tested as an alternative glioma therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we did not observe major differences between PDOXs derived from treatment-naïve and recurrent GBMs. In summary, mouse-derived TME in PDOXs is composed of cellular types relevant to human GBM 4 .…”
Section: Single-cell Rna-sequencing Analyses Identify Major Tme Compo...mentioning
confidence: 99%
“…The brain TME includes endothelial cells, pericytes, astrocytes, neurons, oligodendrocytes and immune cells. Although GBMs are known as 'cold tumors' with very little lymphocytic infiltration 3 , the GBM TME contains up to 40% of myeloid cells, which, as a whole, are referred to as tumorassociated macrophages (TAMs) and are known to create a supportive environment facilitating tumor proliferation, survival and migration 4,5 . TAMs are mainly constituted by brain resident parenchymal microglia (Mg), peripheral monocytes (Mo) and perivascular macrophages, known as border-associated macrophages (BAMs) [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…The cellular and molecular mechanisms of ICI-induced ureteritis/cystitis are not well understood, which precludes their optimal clinical management. Single-cell RNA sequencing (scRNA-seq) offers an opportunity for identifying disease-associated cell subsets and molecular features in human tissues at high resolution and in an unbiased fashion (13). Here, we reported two cases of immune-related ureteritis/cystitis, which were induced by an anti-PD-1 monoclonal antibody (mAb).…”
Section: Introductionmentioning
confidence: 99%